Germline mutations in FH predispose to dominantly inherited uterine fibroids, skin leiomyomata and papillary renal cell cancer. - Tomlinson, I; Alam, N; Rowan, A; Barclay, E; Jaeger, E; Kelsell, D; Leigh, I; Gorman, P; Lamlum, H; Rahman, S; Roylance, R; Olpin, S; et al. (2002)
Uterine leiomyomata (fibroids) are common and clinically important tumors, but little is known about their etiology and pathogenesis. We previously mapped a gene that predisposes to multiple fibroids, cutaneous leiomyomata and renal cell carcinoma to chromosome 1q42.3-q43 (refs 4-6). Here we show, through a combination of mapping critical recombinants, identifying individuals with germline mutations and screening known and predicted transcripts, that this gene encodes fumarate hydratase, an enzyme of the tricarboxylic acid cycle. Leiomyomatosis-associated mutations are predicted to result in absent or truncated protein, or substitutions or deletions of highly conserved amino acids. Activity of fumarate hydratase is reduced in lymphoblastoid cells from individuals with leiomyomatosis. This enzyme acts as a tumor suppressor in familial leiomyomata, and its measured activity is very low or absent in tumors from individuals with leiomyomatosis. Mutations in FH also occur in the recessive condition fumarate hydratase deficiency, and some parents of people with this condition are susceptible to leiomyomata. Thus, heterozygous and homozygous or compound heterozygous mutants have very different clinical phenotypes. Our results provide clues to the pathogenesis of fibroids and emphasize the importance of mutations of housekeeping and mitochondrial proteins in the pathogenesis of common types of tumor.